2019
DOI: 10.1186/s40854-019-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of forecasting methods from selected stock market returns

Abstract: Forecasting stock market returns is one of the most effective tools for risk management and portfolio diversification. There are several forecasting techniques in the literature for obtaining accurate forecasts for investment decision making. Numerous empirical studies have employed such methods to investigate the returns of different individual stock indices. However, there have been very few studies of groups of stock markets or indices. The findings of previous studies indicate that there is no single metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 67 publications
0
59
0
1
Order By: Relevance
“…Besides predictors, forecasting techniques also play an important role in determining forecast accuracy. According to Mallikarjuna and Rao ( 2019 ), traditional regression techniques generally outperform others including artificial intelligence and frequency domain models in providing accurate forecasts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides predictors, forecasting techniques also play an important role in determining forecast accuracy. According to Mallikarjuna and Rao ( 2019 ), traditional regression techniques generally outperform others including artificial intelligence and frequency domain models in providing accurate forecasts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theoretical and empirical studies have revealed that the relation between stock markets and economic growth is positive (Kim et al 2011;Guptha and Rao 2018;Mallikarjuna and Rao 2019). Investment decision plays a significant role in attaining the desired returns through stock market forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that emerging markets usually have high stock returns as compared to developed markets due to noise, less transparent information, and expected market liquidity (Paddrik and Tompaidis 2019). Mallikarjuna & Rao (2019) explains that the forecastability enhances the real value of the stock and if significant, the investors buy the stocks to get a high return. Therefore, forecasting of the stock returns using market ratios is considered significant for investment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusively, the Forecasting Error Statistics of the Emerging Market Level Return outperformed the Market Level Return based on in-sample fit forecastability. The forecast error statistics are found to be dynamically efficient forecast errors to predict the stock returns(Mallikarjuna and Rao, 2019; Caldeira et.al., 2020;Clark et. al., 2020)…”
mentioning
confidence: 99%